2019
DOI: 10.22211/cejem/104684
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Equation of State for the Detonation Products of Emulsion Explosives

Abstract: In this workcylinder testswere performed for two emulsion explosives (Emulinit 8L and Emulinit GM1) used in the mining industry. Based on the results of the tests, the detonation pressure and energy of these explosives were estimated. The detonation characteristics obtained, the profile of the expanding copper tube and the results of the numerical simulation enabled the constants in the JWL(Jones-Wilkins-Lee) equation of state to be determine for the detonation products of these two explosives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…On the other hand, CompNTOR (NTO – 37.5 %, TNT – 30 %, RDX 11 %, Al 14 % & wax – 7.5 % and ρ – 1.73 g cm −3 & VOD 6945 m s −1 ) is initiated by jet. The same team [103] formulated several other formulations based on NTO, TNT, RDX & HMX:…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, CompNTOR (NTO – 37.5 %, TNT – 30 %, RDX 11 %, Al 14 % & wax – 7.5 % and ρ – 1.73 g cm −3 & VOD 6945 m s −1 ) is initiated by jet. The same team [103] formulated several other formulations based on NTO, TNT, RDX & HMX:…”
Section: Resultsmentioning
confidence: 99%
“…The motion was recorded by a high-speed rotating mirror streak camera (writing speed 1.5 mm/μs), using an argon bomb as an illuminator. The experimental detonation velocity D of explosives was measured simultaneously during the cylinder test using the short-circuit sensors method [20].…”
Section: Test Methodsmentioning
confidence: 99%
“…In [4] it is shown that the Jones -Wilkins -Lee equation is used to study explosive processes at high pressures, and the equation in the form of Mie -Grüneisen is applicable to analyze the fluid flow at high pressures. In accordance with [8], the Jones -Wilkins -Lee equation of state finds wide application in analyses of various explosive and, in particular, detonation processes.…”
Section: Introductionmentioning
confidence: 92%